2006
DOI: 10.1089/thy.2006.16.181
|View full text |Cite
|
Sign up to set email alerts
|

On the Prevalence of Familial Nonmedullary Thyroid Cancer in Multiply Affected Kindreds

Abstract: Clinical and genetic studies of familial nonmedullary thyroid cancer (FNMTC) have yielded conflicting results concerning the aggressiveness of the tumors, and uncertainty of their genetic makeup. In most reports of multiply affected families, the composition of the kindreds has favored families of 2 affected members. Using data for differentiated thyroid cancer (DTC) provided by the Surveillance Epidemiology and End Results (SEER) branch of the National Cancer Institute, and fine-needle aspiration data from Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(128 citation statements)
references
References 28 publications
6
117
2
3
Order By: Relevance
“…The identification of FNMTC still relies on clinical data. Therefore, further study investigating the clinical and genetic research should choose the patients with three or more affected members to represent the familial form of the disease in order to reduce the potential selection bias as some authors have recommended (7).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of FNMTC still relies on clinical data. Therefore, further study investigating the clinical and genetic research should choose the patients with three or more affected members to represent the familial form of the disease in order to reduce the potential selection bias as some authors have recommended (7).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective matched-case control study of FNMTC, the majority being PTCs, Maxwell et al (24) reported that familial cases tend to have, but not significantly, improved DFS and disease-specific survival. In a classical study (34), based on probability calculation analysis, Charkes pointed out that up to 60% of familial PTCs diagnosed in families with only two affected members might, actually, represent a fortuitous aggregation of sporadic cases, suggesting that the disease may be more accurately diagnosed in families with three or more affected members (17,21). This fact could, therefore, also contribute to misestimate the aggressiveness of familial PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical estimates suggest that a grouping of two family members with NMTC could represent the concurrence of sporadic tumors, but thyroid tumors in three or more members in kindred, or the diagnosis of PTC in men and children, is more suggestive of a familial predisposition. [24][25][26][27][28][29][30][31][32][33][34][35][36][37]61 Although non-medullary thyroid cancer is mostly sporadic, evidence for a familial form, not associated with other Mendelian cancer syndromes described above (eg FAP and CS), is well documented and thought to cause more aggressive disease. The search for a genetic susceptibility locus for FNMTC started about a decade ago.…”
Section: -58mentioning
confidence: 99%